The Influence of the Problem Based Learning Model on Students' Communication Skills in Biology Learning: Pengaruh Model Problem Based Learning terhadap Kemampuan Komunikasi Peserta Didik pada Pembelajaran Biologi - Wafiq Azizah Ramdani Maarif; Suharsono; Fitriani, Rita (Jurusan Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Timor, 2025)
This study aims to analyze the effect of the Problem-Based Learning (PBL) model on students' communication skills in biology learning for tenth-grade students at SMA Negeri 3 Ciamis. The research employs a quasi-experimental method using a matched-only posttest-only control group design. The population consists of all tenth-grade students at SMA Negeri 3 Ciamis for the 2023/2024 academic year, totaling 376 students across 11 classes. The sample was selected using a purposive sampling technique, with class X-1 assigned as the experimental group and class X-2 as the control group. The research instrument used is a communication skills test comprising eight descriptive questions. Data analysis was conducted using an independent sample t-test. The results indicate that the Problem-Based Learning model significantly influences students' communication skills in biology learning in the 2023/2024 academic year.